Analysis of 24 cases of Transmissible Venereal Tumour (TVT) in two veterinary clinics in Florencia, Colombia - Baldrich-Romero, Nicolás (2021)
The present study analyses the results of 24 complete clinical records of canine transmissible venereal tumour (TVT) obtained in two veterinary clinics in Florencia, Caquetá during 2014 and 2018. The effectiveness of treatments using vincristine sulphate on a weekly basis was greater than 65% after four sessions. Those that used only vincristine sulphate had 50% effectiveness, while those who implemented some type of adjuvant achieved 70% of effectiveness. However, the use of Yatrén (Chiniofon) as immunostimulant was not effective in 3/5 cases. Results showed treatment sessions should continue until after there is no visual evidence of the lesions to eliminate all tumour cells.